Epicardial adipose tissue thickness in newly diagnosed adult onset asthma - Selcuk Baysal, Sadettin; Gunes, Ahmet (Annals of Medical Research, 2021)
Aim: In recent years, asthma, a respiratory disease with an increasing incidence , is often associated with obesity. The parallel increase in the prevalence of asthma and obesity is shown as a reason for this relationship and joint studies are conducted for both diseases. Epicardial adipose tissue (EAT) is a visceral adipose tissue on the pericardium and is associated with visceral obesity rather than general obesity. In this study, we planned to investigate the relationship between asthma and EAT, which is considered as an indicator of visceral adiposity.Material and Methods: The study group consisted of 104 newly diagnosed asthma patients and 99 healthy controls. Transthoracic echocardiography was performed for all participants and EAT was measured.Results: There was no statistically significant difference between baseline clinical and echocardiografic data between groups. Also EAT values were similar in both groups (5.40±0.61 mm in case subjects and 5.29±0.47 mm in healthy subjects ; p=0.142).Conclusion: We did not find any difference between EAT measurements of newly diagnosed adult patients with asthma compared to healthy population.Keywords: Epicardial adipose tissue; echocardiography; obesity; asthma.